Endothelial dysfunction in naval personnel in military activity with obesity - Alvarez Franco, Oscar Luis (2015)
Objective: To establish the level of endothelial dysfunction in naval personnel with obesity in military activity of the Peruvian Navy, also relating the degree of endothelial dysfunction with modifiable factors (diet and physical activity), non-modifiable factors (family history) and cardiovascular stratification. Material and Methods: Endothelial function was analyzed by vascular Doppler, where the flow mediated by dilatation in the brachial artery was evaluated in patients with type I, II and III obesity, at rest, analyzing its relationship with variables such as physical activity, type of diet, family history, age and gender; applying statistical parameters (chi-square and regression analysis) with SPSS. This was a descriptive, prospective, cross-sectional study. Results: A total of 43.4% endothelial dysfunction was found in all age groups, of which 49.3% corresponded to the male sex. Of the total of 173 patients, 56% exercised less than one hour and a total of 113 patients received diets greater than 1800 kcal, finding the presence of endothelial dysfunction in 54% of patients in this group; 65% of patients with a family history presented ED, this being a statistically significant relationship (p<0.05) as was also the case for the evaluation of age, sex and physical activity; diet being a statistically non-significant parameter in the regression analysis. Conclusion: Obese patients evaluated presented a high incidence of endothelial dysfunction, independently of the associated variable to which it was related, since obesity has a direct relationship with the alteration of endothelial function without the presence of pre-existing cardiovascular disease or previous military conditioning. In order to improve the endothelial alteration, it is suggested to perform exercises that contemplate routines longer than one (01) hour, supervised by qualified personnel. Diet, according to the results of the study, plays an important but not determinant role in the influence of endothelial dysfunction. Secondarily, the obese population has an affinity and adherence to overweight and obesity control and nutrition programs, a system that allows the realization of different activities such as physical reconditioning in high-risk patients; however, we see an inverse relationship to these programs on the part of the institution, with the increase of sedentary working conditions that do not favor the proposed exercise routines. Finally, the evaluation of dilation-mediated flow is a marker of cardiovascular disease, which should be considered within the selection techniques for control and follow-up, but above all stratification of the obese patient without cardiovascular disease.